2017
DOI: 10.1371/journal.pone.0184539
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation patterns and gene expression associated with litter size in Berkshire pig placenta

Abstract: Increasing litter size is of great interest to the pig industry. DNA methylation is an important epigenetic modification that regulates gene expression, resulting in livestock phenotypes such as disease resistance, milk production, and reproduction. We classified Berkshire pigs into two groups according to litter size and estimated breeding value: smaller (SLG) and larger (LLG) litter size groups. Genome-wide DNA methylation and gene expression were analyzed using placenta genomic DNA and RNA to identify diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
(54 reference statements)
4
9
0
Order By: Relevance
“…The distribution of DMRs demonstrated here showed that the majority lay within intergenic regions and regions outside CpG Islands/CpG shores. Similar trends have been reported in boar (Hwang et al, 2017;Khezri et al, 2019) and bull (Jiang et al, 2018;Perrier et al, 2018) sperm DNA. Previous research has shown that CpG Islands and CpG shores, in parallel with promoters, play an important role in regulation of transcription (Deaton and Bird, 2011;Long et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…The distribution of DMRs demonstrated here showed that the majority lay within intergenic regions and regions outside CpG Islands/CpG shores. Similar trends have been reported in boar (Hwang et al, 2017;Khezri et al, 2019) and bull (Jiang et al, 2018;Perrier et al, 2018) sperm DNA. Previous research has shown that CpG Islands and CpG shores, in parallel with promoters, play an important role in regulation of transcription (Deaton and Bird, 2011;Long et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…As the DNA methylation status of the promoter and gene body regions could affect gene expression thorough changes in the chromatin structure or transcription efficiency [ 45 , 46 , 47 ], we compared the genome-wide methylation patterns of the control and sense-/antisense tomato fruit to identify the DMRs and investigated the biological functions of the DMRs and DEGs using the GO and KEGG analysis. Forty-three DEGs were found, of which 26 were upregulated and 17 were downregulated in the Sense_vs_Antisense group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently an increasing number of studies have demonstrated that nutritional or environmental changes contribute to changes in inheritable epigenetic modifications, such as DNA methylation (Lan et al, 2013a;Chavatte-Palmer et al, 2018;Kwan et al, 2018;Yuan et al, 2018). As one of the most important and common types of epigenetic modification, DNA methylation plays a significant role in regulating biological processes such as milk production and organ development (Hwang et al, 2017;Fleming et al, 2018;Jessop et al, 2018). In recent years, gene methylation involved in vital biological functions has been wellstudied in animals (Ibeagha-Awemu and Zhao, 2015).…”
Section: Introductionmentioning
confidence: 99%